Fluctuations of ‘mind stuff’ in respect to self (individual) and the external world: Review of a book - 'Concept of Mind and Cognition in Yoga Sutra of Patanjali (YSP)' - Acharya, Bidit (Janaki Medical College Journal of Medical Science, 2021)
No abstract available.